Brand Reputation on Brand Performance in Surplus Indonesia - Lingga Yuliana; Nurliya Apriyana; Didin Hikmah Perkasa; Masnia Masnia; Sully Sia Waty; Aldiwa Pratama; Nadiya Tristi Maria (Universitas Bina Sarana Informatika, 2024)
The research presented here examines the impact of brand reputation on brand performance using the Indonesian Surplus case study. The study employed a quantitative descriptive methodology, surveying one hundred respondents in Jakarta who used the Surplus Indonesia application and purchased goods from partners between July and December 2023. Purposive sampling was used to select the target audience. Data analysis was conducted using Partial Least Square (PLS) with Smart PLS version 4.1 to accurately assess the relationship between brand reputation and brand performance. Respondents answered questionnaires distributed via Google Forms, which included a Likert scale ranging from one to five to measure perceptions of brand reputation and performance. The study's findings indicate that brand reputation has a significant and positive impact on brand performance, highlighting the importance of maintaining a strong brand reputation for business success. The research's management conclusion is that Surplus Indonesia's existence can function as a platform to assist small, medium, and large enterprises in the economy in managing food that is fit for human consumption. In addition, customers are urged to use caution when selecting the goods they wish to use. With the objective to reduce food waste and improve earth's chances of survival.